Elaboración de un plan de emergencia bajo la estructura nfpa 1600 para la empresa Agrinag ubicada en la Ciudad de Latacunga - Molina Arias, Jeferson Mauricio (2023)
The main objective of this research project was to contribute to the development of the emergency and contingency plan proposal under the guidelines of NFPA 1600 for the company Agrinag, for which the preparation of the Emergency Plan was carried out under the Corps format. Santo Domingo Fire Department, where fire and explosion risks were identified by applying specific methodologies such as the NFPA (National Fire Protection Association), MESERI (Simplified Method of Fire Risk Assessment) and Baker methodology (explosion). The research approach is descriptive, it will allow us to analyze the different fire risk factors existing in the different facilities of the Agrinag company, the research design is non-experimental, the population is 120 workers, men and women. Based on the risk values, two MEDIUM RISKS were obtained in the NFPA matrix in two specific areas (Raw Materials Warehouse and Hazardous Waste Warehouse). With the MESERI method the result was IMPORTANT RISK of 4.87, with the Baker methodology from 6.9 meters for eardrum rupture no affectation was seen, while for death from pulmonary hemorrhage from quantities at 0.63 meters No percentages of affected people are observed. Finally, through the application of fire and explosion risk assessments in the Agrinag company, the emergency and contingency plan proposal is left in compliance with the respective processes for its validation and approval.